Hacer visible lo invisible. Intervención en la comunicación del fisioterapeuta como mediador entre la experiencia del paciente y el ortopedista en RTC y RTR. (2020)
Purpose - Understanding the experiential process surrounding total hip and knee replacement at the Lili Valley Foundation. Knowing this, it was proposed to generate a system of patient-medical team communication about the experiential process of patients with RTC and RTR during the post-surgical stage. Likewise, to guarantee a flow of information between the three involved. Design/methodology/approach - The method of experience sampling (ESM) and personal information technology (PI) was used for the immediate collection of experiences and generating changes in users. This extends the scope of a project that covered the whole patient, to focus on the physiotherapist and address a part of the orthopaedist.